Comparative Cytotoxic Activity of Wild Harvested Stems and In Vitro-Raised Protocorms of Dendrobium chryseum Rolfe in Human Cervical Carcinoma and Glioblastoma Cell Lines - Bijaya Pant; Pusp Raj Joshi; Sabitri Maharjan; Laxmi Sen Thakuri; Shreeti Pradhan; Sujit Shah; Sven H. Wagner; Basant Pant (Advances in Pharmacological and Pharmaceutical Sciences)
From the medicinal orchid Dendrobium chryseum Rolfe, which is used in traditional and folk Chinese medicine, the protocorms were raised in Murashige and Skoog (MS) media in three strengths, full strength (FMS), half strength (1/2 MS), and quarter strength (1/4 MS), with or without the phytohormones 6-benzylaminopurine (BAP) and 1-naphthaleneacetic acid (NAA) and coconut water (CW). The comparative cytotoxic activities of the wild and in vitro-raised protocorms were evaluated in human cervical carcinoma (HeLa) and human glioblastoma (U251) cell lines by MTT assay. In in vivo and in vitro, the methanol extracts of D. chryseum showed significant cytotoxic activities. Significant growth inhibition (%) and potent IC50 values were demonstrated in HeLa cell lines (49.79% (210.5 μg/mL) for in vitro-raised Dendrobium chryseum (DCT) versus 46.97% (226.5 μg/mL) for wild Dendrobium chryseum (DCW)). Similarly, activities against U251 cell lines exhibited also significant inhibition (28.76% (612.54 μg/mL) for DCW and 17.15% (1059.92 μg/mL) for DCT). The cytotoxic activities of both, wild and tissue-cultured samples, were superior in HeLa cells. In U251 cells, the wild sample was more active than the tissue-cultured one with a moderate cytotoxic effect. Hence, protocorm culture may therefore be a promising future tool for producing pharmacologically bioactive compounds in medicinal orchids. Such sustainable technology approach will minimize the pressure on the natural population of threatened but commercially important medicinal orchids.